Individual Differences in Psychology Undergraduates' Development of Research Methods Knowledge and Skills. (5th February 2016) - Balloo, Kieran; Pauli, Regina; Worrell, Marcia
Abstract: Not all psychology undergraduates appear to benefit from participating in research methodology classes. This longitudinal study tracked how students' knowledge of research methods developed throughout their three-year undergraduate psychology degree. Card sorting procedures measuring knowledge of research methods terminology were repeated at four time-points across three years then analyzed using multidimensional scaling. There was no significant improvement in students' research methods structural knowledge after a year, but there was by the end of students' second year. Knowledge did not improve after students' final year of study. Various metacognitive and motivational variables were significant correlates of research methods knowledge and research skills. Structural knowledge of research methods terminology appears to be developed from formal methodology training and is not improved upon after completion of a final year research project dissertation. Improving metacognitive skills and increasing motivation for methodology classes may be linked to better development of research methods knowledge and research skills.